The Influence Of Strategic Orientation Dimensions On Market Performance During Covid-19 Pandemic: A Study Of Culinary Business In Kendari City, Indonesia - Indri Hapsari; Yunitawati Lampasa; Marjani Marjani; Juwita Juwita; Hairudin Bugis (Politeknik APP Jakarta, 2022)
This study aimed to analyze the effect of the strategic orientation dimension on the culinary business market performance in Kendari City during the Corona Virus Disease Pandemic. The method used was descriptive quantitative with a non-probability sampling approach with purposive sampling technique. The population was culinary business actors who still survive and have been running for the business more than 2 years during the COVID-19 pandemic. The sample in this study only obtained 38 respondents. The data analysis technique in this research was path analysis using SmartPLS VS 3.0. The results showed an analysis of the strategic dimensions that have an aggressive attitude and had significant effect on market performance so that culinary business actors can improve their market performance during the COVID-19 pandemic.